Republic of Palau : Staff Report for the 2012 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2012)
This 2012 Article IV Consultation reports that Palau's growth is expected to be favorable at 3 percent in FY2012 and to average 2 percent over the medium term. The outlook is clouded by an unsettled global environment, and downside risks dominate. Highly dependent on tourism, imports of food and fuel, and foreign aid, Palau remains vulnerable to external headwinds and has limited policy space to counter these risks. The authorities have made commendable efforts to reduce the current fiscal deficit markedly during FY2010-11, but the deficit remains sizable.